Return-To-Sport at 5-Year Follow-Up after Non-Operative Treatment of Acute Achilles Tendon Rupture. Issue 4 (16th October 2019) - Krause, Fabian; Schwinghammer, Andreas; Lerch, Till; Schmid, Timo; Ecker, Timo; Schmaranzer, Florian; Weber, Martin
Category: Sports Introduction/Purpose: There is a controversy if non-operative or operative treatment for acute Achilles tendon rupture is superior. It is unknown, if young and active patients with acute Achilles tendon rupture, return to previous sports activity level after treatment with standardized non-operative immediate full weight-bearing protocol. The purpose of this was to assess (1) the return-to-sport rate and subjective satisfaction in patients with different activity levels before the rupture, at 1-year, and at 5-year follow-up, (2) the clinical outcome at 1-year follow-up, and (3) re-ruptures and complications. Methods: Out of 171 consecutive patients that were treated nonoperatively, 114 patients were available for 1-year follow-up. Eighty-nine patients responded to questionnaires for sports activity. Non-operative treatment consisted of a combination of an equinus cast and rehabilitation boot, that enables immediate full weight-bearing and early functional rehabilitation. Clinical 1-year follow-up and follow-up with questionnaires at 1-year and 5-year follow-up were evaluated to calculate Tegner Activity Scale (TAS), and Activity Rating Scale (ARS) and were compared to the status before the rupture. Based on the TAS before the rupture, patients were divided into a low-level activity (<5) and high-level activity (>5) group and the return-to-sport rate was compared between those two groups.Clinical assessment at minimum 1-year follow-up included testing of plantarflexion strength and endurance, calf circumference, and subjective parameters to calculate a modified Thermann score. Mean clinical follow-up was 34 ± 23 months (range 12-88 months). Results: (1) A significantly higher proportion (91%) of the patients in the low-level activity group returned to their previous TA at 5-year follow-up compared to patients (67%) in the high-level activity group (p=0.029). A higher proportion (91%) of the patients in the low-level activity group returned to their previous ARS Score at 5-year follow-up compared to patients (82%) in the high- level activity group (p=0, 115). (2) The mean Thermann score was not significantly different between the two activity groups at minimum 1-year follow-up: 84 ±12 (range, 41-100) and 82 ±12 (range, 44 -100). (3) There were a total of 17 complications. There were 9, 6% reruptures (8 with and 3 without an adequate trauma), 5 deep venous thromboses, 1 complex regional pain syndrome at 1 year follow-up. Conclusion: After 17 years of prospective evaluation, our non-operative treatment protocol for acute rupture of the Achilles tendon leads to good functional outcome, high patient satisfaction and high return-to-sport rate. Most patients return to their previous sports activity level after a standardized nonoperative early full-weightbearing treatment protocol for acute Achilles tendon rupture. Even for patients with a high activity level return to pre-rupture sports level activity was possible in two third of the patients. The re-rupture rate with immediate weight bearing is low and comparable to other non-operative treatment methods.